2012
DOI: 10.1042/bj20120377
|View full text |Cite
|
Sign up to set email alerts
|

Human YKL-39 is a pseudo-chitinase with retained chitooligosaccharide-binding properties

Abstract: The chitinase-like proteins YKL-39 (chitinase 3-like-2) and YKL-40 (chitinase 3-like-1) are highly expressed in a number of human cells independent of their origin (mesenchymal, epithelial or haemapoietic). Elevated serum levels of YKL-40 have been associated with a negative outcome in a number of diseases ranging from cancer to inflammation and asthma. YKL-39 expression has been associated with osteoarthritis. However, despite the reported association with disease, the physiological or pathological role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 49 publications
(70 reference statements)
0
42
0
1
Order By: Relevance
“…MembersSuperimposition of the structure of the wild-type YKL39⅐ GlcNAc) 6 complex obtained in this study on that of YKL39⅐GlcNAc 6 complex (4AY1) reported by Schimpl et al (27) results in a root mean square deviation of 0.22 for C␣ positions over 334 atoms (Fig. 5).…”
Section: Structural Comparison With Other Human Gh-18mentioning
confidence: 99%
See 3 more Smart Citations
“…MembersSuperimposition of the structure of the wild-type YKL39⅐ GlcNAc) 6 complex obtained in this study on that of YKL39⅐GlcNAc 6 complex (4AY1) reported by Schimpl et al (27) results in a root mean square deviation of 0.22 for C␣ positions over 334 atoms (Fig. 5).…”
Section: Structural Comparison With Other Human Gh-18mentioning
confidence: 99%
“…All diffraction data were indexed, integrated, and scaled using the program HKL2000 (29), and molecular replacement was employed to obtain phase information using the program MOLREP from the CCP4 suite (30). The structure of YKL-39 bound to GlcNAc 2 was solved using the previously published structure of YKL-39 in complex with GlcNAc 6 (PDB code 4AY1) as the search model (27). Other data sets, including ligand-free YKL-39 and YKL-39 in complex with GlcNAc 4 and GlcNAc 6 , were solved using the final structure of the YKL-39⅐GlcNAc 2 complex as the model for rigid body refinement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such seemingly inactive glycoside hydrolase mutants in which catalytic residues have been replaced are an increasingly uncovered phenomenon, particularly in the case of chitinases, and generally thought to represent simple binding domains (10,11). Indeed, through fluorescence perturbation studies, the authors (5) measure weak but progressively tighter binding of β-1,6-GlcNAc oligomers of increasing size, whereas chito-oligosaccharides are shown not to bind.…”
mentioning
confidence: 99%